International Legal Challenges in Regulating the Use of Artificial Intelligence for Military and Peacekeeping Purposes - Dagen, Tomislav (Review of European and Comparative Law, 2025)
On the treshold of the Fifth Industrial Revolution, the global security order is facing renewed instability, marked by the proliferation of armed conflicts and wars. Emerging technologies, particularly artificial intelligence (AI), are increasingly viewed both as tools of military superiority and as potential disruptors of peace. This paper examines whether AI can and should be developed as an instrument of international law (de lege ferenda) to prevent and end armed conficts, or whether current trajectories in technological advancement are predominantly oriented toward military applications, thereby generating future hostilities and risking violations of international humanitarian law. Through a comparative and analytical approach, the study argues that, despite the erosion of trust in international law, sustainable peace mechanisms must remain rooted in the human dimension, which continues to be the decisive factor in implementing legal norms governing the cessation of hostilities (de lege lata).